2020
DOI: 10.1007/s11557-020-01617-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphaeropsis sapinea and fungal endophyte diversity in twigs of Scots pine (Pinus sylvestris) in Germany

Abstract: Sphaeropsis sapinea is the causal fungal agent of Diplodia tip blight disease of Scots pine (Pinus sylvestris) and other coniferous trees of relevance to forestry in Germany. In this study, the distribution and occurrence of S. sapinea and accompanying endophytic fungi in twigs of healthy and diseased Scots pine was investigated on a spatial and temporal scale. Sampling of 26,000 twig segments from trees in 105 temperate coniferous forest stands in Germany resulted in isolation of 33,000 endophytic fungi consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 103 publications
7
73
4
Order By: Relevance
“…The five most abundant fungal taxa from our study of early season organs were Alternaria, Cryptococcus, Hymenoscyphus, Herpotrichia, and Tetracladium, respectively. In pine, twigs were rich in Pleosporales fungi, e.g., Alternaria (Bußkamp et al, 2020). Hymenoscyphus and Lachnum were only found in buds whereas Candida, Chaetomium, Itersonilia, Setomelanomma, Sterigmatomyces, and Sistotrema were only found in twigs.…”
Section: Temporal Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five most abundant fungal taxa from our study of early season organs were Alternaria, Cryptococcus, Hymenoscyphus, Herpotrichia, and Tetracladium, respectively. In pine, twigs were rich in Pleosporales fungi, e.g., Alternaria (Bußkamp et al, 2020). Hymenoscyphus and Lachnum were only found in buds whereas Candida, Chaetomium, Itersonilia, Setomelanomma, Sterigmatomyces, and Sistotrema were only found in twigs.…”
Section: Temporal Effectsmentioning
confidence: 99%
“…(Martín-García et al, 2011), Pinus sp. (Botella et al, 2010;Sanz-Ros et al, 2015;Bußkamp et al, 2020), Abies concolor, and Picea abies (Sieber, 1989). Twig mycobiomes associate with both biotic and abiotic factors, e.g., air quality (Bakys et al, 2009), geography and seasonality (Göre and Bucak, 2007), genotype and growth (Lamit et al, 2014;Sanz-Ros et al, 2015), and plant health (Sieber, 1989;Ragazzi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The primary endophytic fungal species from unhealthy uninfested and S. noctilio infested trees were also similar, such as S. sapinea, T. atroviride, O. minus. The results of Simpson dominance index showed that fungal communities had a high concentration in unhealthy uninfested trees compared with the other two samples trees, and healthy uninfested trees has higher fungal diversity 24 (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…and widely distributed in Pinus radiata plantations in northern Spain, outbreaks of which have a considerable impact on plantations 23 . It was recognized as the most widespread necrotrophic ascomycete pathogen responsible for dramatic losses of pine trees across the continents 24 . S. sapinea has emerged as an aggressive fungal pathogen all over the world and could directly invade the young shoots of pine trees [25][26][27] .…”
mentioning
confidence: 99%
See 1 more Smart Citation